2006
DOI: 10.1029/2005gl024715
|View full text |Cite
|
Sign up to set email alerts
|

A GCM study of the influence of equatorial winds on the timing of sudden stratospheric warmings

Abstract: A full troposphere‐stratosphere‐mesosphere global circulation model is used in a set of idealised experiments to investigate the sensitivity of the Northern Hemisphere winter stratospheric flow to improvements in the equatorial zonal winds. The model shows significant sensitivity to variability in the upper equatorial stratosphere, the imposition of SAO and QBO like variability in this region advances the timing of midwinter sudden warmings by about one month. Perturbations to the lower equatorial stratosphere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
55
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 21 publications
7
55
1
Order By: Relevance
“…The HTE also holds when the QBO is defined by the vertical wind shear between 50 and 70 hPa, but it tends to be weaker for the QBO defined at other levels (Hitchman and Huesmann 2009, hereafter HH09). The HTE has been confirmed by observational studies (e.g., Dunkerton and Baldwin 1991;Naito and Hirota 1997;Lu et al 2008Lu et al , 2014 as well as by both mechanistic (e.g., O'Sullivan and Young 1992; Naito and Yoden 2006;Pascoe et al 2006) and complex general circulation models (e.g., Calvo et al 2009;Marshall and Scaife 2009). However, the mechanism behind the HTE is still under debate (e.g., Naoe and Shibata 2010;Yamashita et al 2011;Garfinkel et al 2012;Lu et al 2014).…”
Section: Introductionmentioning
confidence: 70%
“…The HTE also holds when the QBO is defined by the vertical wind shear between 50 and 70 hPa, but it tends to be weaker for the QBO defined at other levels (Hitchman and Huesmann 2009, hereafter HH09). The HTE has been confirmed by observational studies (e.g., Dunkerton and Baldwin 1991;Naito and Hirota 1997;Lu et al 2008Lu et al , 2014 as well as by both mechanistic (e.g., O'Sullivan and Young 1992; Naito and Yoden 2006;Pascoe et al 2006) and complex general circulation models (e.g., Calvo et al 2009;Marshall and Scaife 2009). However, the mechanism behind the HTE is still under debate (e.g., Naoe and Shibata 2010;Yamashita et al 2011;Garfinkel et al 2012;Lu et al 2014).…”
Section: Introductionmentioning
confidence: 70%
“…It is also increasingly apparent that successful modelling of the equatorial semi-annual oscillation and the QBO (e.g. Pascoe et al, 2006) are important for improved characterization of global wind, temperature and PW fields at extratropical latitudes. Such studies would be extremely valuable, as these issues indicate that modelled PW-GW-polar vortex characteristics and wave-interactions are not in fully realistic balance in some models.…”
Section: Summary and Commentsmentioning
confidence: 99%
“…Both QBO and SAO have an effect on the tracer transport in the stratosphere (e.g., Huang et al, 2008;Punge et al, 2009;Khosrawi et al, 2013;Shu et al, 2013). Further, the QBO has an effect on the stability of the polar vortex (e.g., Holton and Tan, 1980), and there are indications that both QBO and SAO have an influence on the timing of sudden stratospheric warmings (e.g., Pascoe et al, 2006). It has been found that the QBO has an effect on the weather and climate in the lower atmosphere and even at the surface (e.g., Ebdon, 1975;Boer and Hamilton, 2008;Marshall and Scaife, 2009).…”
Section: Introductionmentioning
confidence: 99%